(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2023)
In 1780 the English translator and essayist Eliza Ball Hayley (b.1750-1797) published Essays on Friendship and Old-Age, by the Marchioness de Lambert. The text was a translation of two of the many philosophical treatises written by the French philosopher Anne-Thérèse de Lambert (1647-1733). Addressing the chronological, linguistic, and geographical distance between the two authors and their philosophical thought, this article examines the motivations behind Hayley’s translation, regarding them as an act of resistance to the predominant contemporary male intellectual discourse, dismissive of de Lambert’s influence. Furthermore, it suggests that, through the act of translating, Hayley is in fact recovering de Lambert and her (gendered) contribution to the history of ideas, while in parallel she is asserting her own place within this intellectual continuum by benefiting from de Lambert’s legacy, and thus contributing to, and sustaining, a female genealogy of thought.